Proceso atención de enfermería en embarazada de 38.2 semanas de gestación más desproporción cefalopélvica factor materno. - Guambuguete Barreto, Margarita Elizabeth (2024)
Cephalo-pelvic disproportion (CPD) occurs when the size of the fetus's head and the mother's pelvis are not compatible, preventing vaginal delivery despite adequate contractions. This condition can create risks for both the mother and the baby, it can also increase the rate of endomyometritis or decrease fetal pH and prolong hospital stay. For its diagnosis, clinical methods are used, including X-ray pelvimetry, tomography, ultrasonography and magnetic resonance imaging. This case study addresses the nursing care provided to a pregnant patient at 38.2 weeks of gestation with PCD and inadequate contractions, applying Marjory Gordon's theory of functional health patterns to create a personalized care plan.